Adverse Effects of Ramadan Fasting in a Girl with Salt-Losing Congenital Adrenal Hyperplasia - Valeria Calcaterra; Francesco Bassanese; Andrea Martina Clemente; Rossella Amariti; Corrado Regalbuto; Anna Sala; Gian Vincenzo Zuccotti (Case Reports in Endocrinology)
Objective. Congenital adrenal hyperplasia (CAH) is the most common cause of adrenal insufficiency in pediatrics. Chronic glucocorticoid replacement is the mainstay of treatment in the classic forms of CAH, and mineralocorticoid replacement therapy is mandatory in the salt-wasting form. Fasting is a mild stressor, which can expose to dehydration, hypotension, hypoglycemia, and acute adrenal crisis in patients with adrenal insufficiency. Case. We report the case of an adolescent affected by the classic form with salt-losing CAH, who observed Ramadan for 30 days, without individualized therapeutic management plan. After Ramadan, a dramatic increase of ACTH level (1081 pg/ml, n.v. 6–57), reduced cortisolemia, tendency to hypotension, and weight loss were recorded. She experienced insomnia, intense thirst, asthenia, and headache. The symptoms disappeared restarting the previous therapy schedule and increasing the total hydrocortisone daily dose with progressive restoring of hormonal control. Conclusion. Our case confirms that patients with CAH are vulnerable, especially during fasting in Ramadan, with a higher risk of acute adrenal crisis. CAH patients should reform and individualize their treatment plan and be submitted to careful monitoring.